2020
DOI: 10.1152/ajpendo.00120.2020
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration in juvenile Iberian pigs with diet-induced nonalcoholic fatty liver disease

Abstract: The objective of this study was to investigate whether juvenile Iberian pigs with diet-induced non-alcoholic fatty liver disease (NAFLD), cholestasis and gut dysbiosis would develop histological and metabolic markers of neurodegeneration in the frontal cortex (FC), and whether supplementing probiotics would influence the response to the diet. Twenty-eight juvenile Iberian pigs were fed for 10 weeks either a control (CON) or high-fructose high-fat diet (HFF) with or without a commercial probiotic mixture. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 72 publications
4
29
0
2
Order By: Relevance
“…The plasma level of quinolinate, a precursor for nicotinamide adenine dinucleotide (NAD + ) synthesis, was significantly downregulated only in subjects with moderate steatosis vs no steatosis (Figure 4C). It has been reported that downregulation of quinolinate is associated with NAFLD in animals (Zeltser et al , 2020), and the altered NAD + metabolism is associated with NAFLD in humans (Mardinoglu et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The plasma level of quinolinate, a precursor for nicotinamide adenine dinucleotide (NAD + ) synthesis, was significantly downregulated only in subjects with moderate steatosis vs no steatosis (Figure 4C). It has been reported that downregulation of quinolinate is associated with NAFLD in animals (Zeltser et al , 2020), and the altered NAD + metabolism is associated with NAFLD in humans (Mardinoglu et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Concordantly, in a small study, Filipovic et al showed that reduced brain volume in patients with NAFLD was associated with poor cognitive performance [35]. In a juvenile minipig model of diet-induced NAFLD, neurodegeneration was demonstrated as neuronal loss and astrogliosis in the frontal cortex, compared with control pigs [127].…”
Section: Neurodegenerationmentioning
confidence: 93%
“…Approval for all experimental procedures was obtained from the Institutional Animal Care and Use Committee of California State University (#1611) before experiments began, and all procedures were in compliance with the National Research Council Guide for the Care and Use of Laboratory Animals. Two previous publications characterized the Iberian pig NAFLD phenotype in terms of liver and gut histology, biochemistry, blood, and metabolomics [21] and documented impairment of neurogenesis in the cerebral frontal cortex [22].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, 43% of CON and 17% of HFF-fed pigs developed steatosis without inflammation and/or cellular ballooning, and 57% of the CON group had no lesions in the liver. Further, HFF-fed pigs presented gut dysbiosis and hyperplasia that were positively correlated with the severity of the hepatic injury, as well as metabolic changes in liver, plasma, and colon digesta consistent with choline depletion and dysregulation of one-carbon metabolism [21,22]. Compared to CON, HFF-fed pigs had decreased cholesterol (p ≤ 0.01), and high and low-density lipoproteins (p ≤ 0.05), whereas triglycerides, non-esterified fatty acids, leptin, and pro-inflammatory cytokines TNF-α, IL-1α, and TNF-β did not differ across groups.…”
Section: Liver Histology Serum Biochemistry and Body Compositionmentioning
confidence: 99%
See 1 more Smart Citation